Recent advancement of bioinspired nanomaterials and their applications: A review - Wu, Gang; Hui, Xiaodan; Hu, Linhui; Bai, Yunpeng; Rahaman, Abdul; Yang, Xing-Fen; Chen, Chunbo (Frontiers in Bioengineering and Biotechnology, 2022)
With the advancement in the field of nanotechnology, different approaches of synthesis of nanomaterials have been formulated, among which the field of bioinspired or biomimetic nanoplatforms have been utilized for different biomedical applications. In this context, bioinspired or biomimetic nanoparticles (NPs) have been synthesized in which the inspiration of synthesis is taken from the nature or its components. Innovations in the bioengineering tools and bio-conjugation chemistry have enabled scientists to develop novel types of such nanoplatforms. They have several advantages over normal synthesis protocols. This review summarized the synthesis of bioinspired NPs and their enhanced therapeutic effects by giving critical emphasis on the current work done in this field, which may open up new windows for synthesis of novel NPs for their potential applications in biomedical sciences.